Self-Tuning Fuzzy PI-Type Controller in Z-Source Inverter for Hybrid Electric Vehicles - Pham Cong Thanh; AnWen Shen; Phan Quoc Dzung; Nguyen Bao Anh; Le Hoang Viet (Institute of Advanced Engineering and Science, 2012)
This paper presents new algorithms to control speed induction motor (SIM) and the peak dc-link voltage (PDV) across the inverter bridge in z-source inverters (ZSI) by applying self-tuning fuzzy PI controller (SFP) with robust structure and non-linear characteristic. In particular, this so-called SFP based control algorithm (SFPA) is applied to a closed loop speed controlsystem of induction motor, which relies on direct torque controlscheme combined with modified space vector modulation (DTCMSVM) control strategy with so many exceptional features (e.g. fast torque response, low steady state torque ripple, and high accurate). Additionally, SFPA is used to control SIM and PDV are more adaptive to the sudden change of parameters such as load torque, stator resistance and dc input voltage (DIV), respectively. The transient response of SIM and PDV are thus improved with less over shoot, short rise time, small steady-state error and fast settling time, with low disturbance for output voltage stabilization in the inverter bridge. As a result, we achieve higher accuracy and robustness of SIM control system. Our new SFPA is verified in both simulation and experimental implementation using MATLAB and dSPACE DS1103, respectively.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.571